TYPOLOGICAL FEATURES OF THE NEWSPAPER “ KARAKALPAKSTAN TONGGI” - Srajatdinov Akmal Kutlimurat ugli (International Journal of Innovations in Engineering Research and Technology, 2021)
The article analyzes briefly the main pages of the political publication, in order to reveal the peculiarities of “ Karakalpakstan Tonggi” newspaper published in Karakalpakstan and to show its content.